2000
DOI: 10.1002/1522-2683(20000701)21:13<2610::aid-elps2610>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Towards higher resolution: Two-dimensional Electrophoresis ofSaccharomyces cerevisiae proteins using overlapping narrow immobilized pH gradients

Abstract: The rising number of proteome projects leads to new challenges for two-dimensional electrophoresis with immobilized pH gradients and different applications of this technique. Not only wide pH gradients such as 4-12 or 3-12 (Görg et al., Electrophoresis 1999, 20, 712-717) which can give an overview of the total protein expressions of cells are in demand but also overlapping narrow immobilized pH gradients are to be used for more specialized and detailed research and micropreparative separations. The advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(50 citation statements)
references
References 16 publications
(7 reference statements)
1
49
0
Order By: Relevance
“…Some of these preparative methods do not yield high-resolution separations and/or do not produce sufficiently small sample volumes for direct application to analytical 2-D gels at high protein loads. A conceptually attractive alternative to sample prefractionation is direct analysis of samples using multiple narrow pH range IPG gels in parallel [16][17][18]. The main benefits of narrow IPG gradients are that the total number of protein spots per pH unit can be increased substantially due to higher spatial resolution of different protein spots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these preparative methods do not yield high-resolution separations and/or do not produce sufficiently small sample volumes for direct application to analytical 2-D gels at high protein loads. A conceptually attractive alternative to sample prefractionation is direct analysis of samples using multiple narrow pH range IPG gels in parallel [16][17][18]. The main benefits of narrow IPG gradients are that the total number of protein spots per pH unit can be increased substantially due to higher spatial resolution of different protein spots.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sample cup loading rather than gel rehydration loading could potentially reduce artifacts caused by precipitation of proteins with pIs outside narrow pH range IPG gels, since these proteins only contact the gel at the sample loading site [17]. However, sample cup loading methods can be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…They estimate that the increase in resolution allowed for the detection of proteins present at only about 300 copies per cell. Wildgruber et al [46] compared the collective use of IPG strips with pH ranges of 4-5, 5-6, and 5.5-6.7 against gels run with IPG strips with pH ranges 3-10 and 4-7. They found that they were able to detect 2.3 and 1.6 times more protein spots using the narrow-range gels than with the IPG 3-10 and 4-7 gels, respectively.…”
Section: The Modern Approachesmentioning
confidence: 99%
“…Overlapping spots were only counted once. Reprinted from [46], with permission. dimensional separation technique for the analysis of proteome mixtures.…”
Section: The Modern Approachesmentioning
confidence: 99%
“…Alternatively, a proteomics approach would be useful for functional genomics studies. While 2-DE has been widely used to study the proteome of a number of industrially relevant organisms [6], including both bacteria [7] and yeast [8], only very few reports on 2-DE of filamentous fungi are available, and these are typically strains of medical [9] verses industrial importance.…”
Section: Introductionmentioning
confidence: 99%